Penerapan Teknologi Rocket Stove untuk Mengurangi Polusi Pembakaran Sampah di Kampung Merangkai - Pradipa, Raditya; Gunawan, Rahmad; Alfiah Insani Amin, Andi Nur; Yuliskania, Aisyara; Tania, Manzilah Ditiara; Harmawan, Muhamad Rizki; Jasmin, Muhammad Iqbal; Nugroho, Altaric; Fadilla, Niken Rahma; Vania, Azra Gusti; Avicenna, Achyar Zein; Nofrial, Nofrial; Razkia, Binta; Nadira, Besti Zahratul (LPPM UMRI, 2025)
Ineffective plastic waste management remains a significant problem in rural communities, particularly due to traditional burning practices that generate air pollution, odors, and health risks. The Muhammadiyah ‘Aisyiyah Community Service Program (KKNMAs) in Merangkai Village, Dayun District, Siak Regency aimed to provide an alternative solution through the application of appropriate technology in the form of a rocket stove. The implementation method consisted of preparation (literature study, field observation, and design), execution (socialization, construction of a rocket stove unit, and technical training), and evaluation (monitoring, interviews, and design improvements). The results indicated that the rocket stove reduced smoke and odor emissions by 60–80% compared to traditional burning, improved efficiency in processing dry waste, and encouraged active community participation in environmental management. Success factors included technology design, support from local government, and community awareness, although the limited number of units remained a challenge. This program demonstrated that rocket stove technology offers a sustainable small-scale waste management solution with potential replication in other rural areas.